Strabismus Is Correlated with Gross Motor Function in Children with Spastic Cerebral Palsy. (2nd November 2019) - Jeon, Hyeshin; Jung, Jae Ho; Yoon, Jin A; Choi, Heeyoung
ABSTRACT: Purpose : To investigate the correlation between clinical features of strabismus and motor dysfunction classified according to the Gross Motor Function Classification System (GMFCS) in patients with spastic cerebral palsy (CP). Methods : In this retrospective, cross-sectional study in single tertiary medical center, 62 patients who are diagnosed with spastic CP who had an ophthalmic examination between 2006 and 2014 were included. Only patients with vision sufficient to fixate were included and patients with restrictive or paralytic strabismus were excluded. The types of CP were classified as diplegia, hemiplegia, or quadriplegia for distribution of motor impairment. The GMFCS was used to grade gross motor dysfunction, which was then classified as mild (grade 1, 2 and 3) or severe (grade 4 and 5) motor impairment. Strabismus was investigated in terms of direction, constancy, and deviation angle. The relationship between strabismus characteristics and the level of GMFCS and type of CP were assessed. Results : Thirty-eight and 24 patients had mild or severe motor deficit, respectively. Forty patients had strabismus, which was more frequent in patients with severe motor impairment.(P = .014) Exotropia and esotropia occurred with similar frequency. Constant and large-angle strabismus was frequently observed in patients with severe motor impairment.(P < .005, 0.027) The topographical subtype of CP was not related to clinical features of strabismus. Conclusions : The prevalence of strabismus is higher in severe motor impairment. The constancy and angle of strabismus was related to the severity of motor impairment while the topographical subtype of CP has no significant relationship.